Granting Of Criminal Sanctions Against Children Consumpting Narcotics - Ediwan, Elche Angelina; Parmono, Budi; Muhibbin, Moh. (Scholar Center, 2023)
This research aims to describe the regulation of Narcotics criminal acts according to positive law in Indonesia and those responsible for criminal sanctions against children who use Narcotics according to Law Number 35 of 2009 concerning Narcotics’ This research is normative legal research, descriptive in nature, statutory approach, consisting of primary, secondary and tertiary legal materials. Qualitative analysis is carried out systematically in order to get answers to problems. The results of the study stated that the regulation of narcotics crimes began with Law No. 9 of 1976 which prohibited the manufacture, storage, distribution and use of narcotics. Then Law No. 22 of 1997 with a wider scope, the criminal threat is made worse in the form of the death penalty. Then Law no. 35 of 2009, prohibits possessing, storing, controlling or providing Narcotics and Narcotics Precursors; the act of producing, importing, exporting, or releasing Narcotics and Narcotics precursor; acts in the form of offering to sell, sell, buy, receive, become an intermediary in buying and selling, exchanging, or handing over Narcotics and Narcotics precursors; and acts in the form of bringing, sending, transporting or transiting Narcotics and precursors. Criminal sanctions for children who use Narcotics are regulated in Law No. 3 of 1997 concerning Juvenile Courts and Law No. 35. Children who commit Narcotics crimes can be sentenced under Article 127 of Law No. 35 of 2009 in conjunction with Article 22 of Law No. 3 of 1997 amended to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System. Prison sentence that can be written off for Narcotics children is no longer than ½ (one half) of the maximum prison sentence for adults.